P2Y receptors on astrocytes and microglia mediate opposite effects in astroglial proliferation - Clara Quintas (2011)
Nucleotides released upon brain injury signal to astrocytes and microglia playing an important role in astrogliosis, but the participation of microglia in the purinergic modulation of astrogliosis is still unclear. Highly enriched astroglial cultures and co-cultures of astrocytes and microglia were used to investigate the influence of microglia in the modulation of astroglial proliferation mediated by nucleotides. In highly enriched astroglial cultures, adenosine-5'-triphosphate (ATP), adenosine 5'-O-(3-thio)-triphosphate (ATP gamma S), adenosine 5'-O-(3-thio)-diphosphate (ADP beta S; 0.01-1 mM), and adenosine-5'-diphosphate (ADP; 0.1-1 mM) increased proliferation up to 382%, an effect abolished in co-cultures containing 8% of microglia. The loss of ATP proliferative effect in co-cultures is supported by its fast metabolism and reduced ADP accumulation, an agonist of P2Y(1,12) receptors that mediate astroglial proliferation. No differences in ADP beta S and ATP gamma S metabolism or P2Y(1,12) receptors expression were found in co-cultures that could explain the loss of their proliferative effect. However, conditioned medium from microglia cultures or co-cultures treated with ADP beta S, when tested in highly enriched astroglial cultures, also prevented ADP beta S proliferative effect. None of the uracil nucleotides tested had any effect in proliferation of highly enriched astroglial cultures, but uridine-5'-triphosphate (UTP; 0.1-1 mM) inhibited proliferation up to 66% in co-cultures, an effect that was dependent on uridine-5'-diphosphate (UDP) accumulation, coincident with a co-localization of P2Y(6) receptors in microglia and due to cell apoptosis. The results indicate that microglia control astroglial proliferation by preventing the proliferative response to adenine nucleotides and favouring an inhibitory effect of UTP/UDP. Several microglial P2Y receptors may be involved by inducing the release of messengers that restrain astrogliosis, a beneficial effect for neuronal repair mechanisms following brain injury.